Helicobacter pylori Eradication Efficacy of Therapy Based on the Antimicrobial Susceptibility in Children with Gastritis and Peptic Ulcer in Mekong Delta, Vietnam - Loan T. T. Le; Tuan A. Nguyen; Nghia A. Nguyen; Yen T. H. Nguyen; Hai T. B. Nguyen; Liem T. Nguyen; Mai T. Vi; Thang Nguyen (MDPI AG, 2022)
Background: The efficacy of Helicobacter pylori (H. pylori) eradication therapy for children is currently low, and antibiotic resistance is a significant cause of treatment failure. The purpose of this study was to evaluate the H. pylori eradication efficacy of therapy based on antimicrobial susceptibility in pediatric patients with gastritis and peptic ulcer. Methods: This study was conducted at Can Tho Children's Hospital and Can Tho University of Medicine and Pharmacy Hospital between March 2019 and April 2022. We performed an upper gastrointestinal endoscopy, cultured H. pylori from biopsies of gastric mucosa, determined antibiotic sensitivities to H. pylori by the E-test method, and treated eradication based on the antibiotic susceptibilities of bacteria. After at least 4 weeks of eradication therapy, we assessed the effectiveness of treatment with a breath test. Results: Among 237 children recruited in this study, 48.9% were boys and 51.1% were girls, and the mean age was 10.03 ± 2.53 years. We determined that 80.6% of H. pylori were resistant to clarithromycin, as well as amoxicillin, metronidazole, levofloxacin, and tetracycline, at 71.7%, 49.4%, 45.1%, and 11.4%, respectively. The overall eradication rate of H. pylori was 83.1% (172/207). Among therapies tailored to antimicrobial susceptibility, the bismuth quadruple regimen achieved the greatest success, but the efficacy of triple therapy with esomeprazole + AMX + CLR/MTZ was low. Conclusions: Tailored eradication therapy was highly successful in our study but did not achieve over 90%. We recommend that in countries with a high prevalence of antibiotic resistance in H. pylori strains, particularly where the amoxicillin-resistance rate of H. pylori is high, therapy tailored to antimicrobial susceptibility should be used as first-line therapy, and bismuth and tetracycline should be added to enhance the eradication efficacy in children.